Peculiarities of the terminological field of the study of the problem of formation of the pedagogical culture of future officers of the Ground Forces of the Armed Forces of Ukraine - Sevruk, Viacheslav (Journal of Education, Health and Sport, 2021)
The article is devoted to highlighting the peculiarities of the terminological field of research on the problem of formation of the pedagogical culture of future officers of the Ground Forces of the Armed Forces of Ukraine. Humanitarian training is an important aspect of military education. It is necessary to determine the peculiarities of the formation of the pedagogical culture of future officers.